Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
Audience: John Krebs Hon. Stephen Henry, Hon. James Ardaiz, Jeff Kuhn and John Slutter with beards, Hon. Steven Vartabedian among others A